Perencanaan dan Perancangan Objek Wisata Situ Rawa Binong dengan Konsep Arsitektur Ekologi di Desa Hegarmukti - Retno Fitri Astuti; Jaka Bahrunaya Marbun (Prosiding Sains dan Teknologi, 2022)
One of the exact areas in Bekasi Regency which has a tourist spot that is still maintained to its natural beauty, namely Situ Rawa Binong. The location of Situ Rawa Binong itself is in the center of the crowd of industrial factories and many other activities such as students and students studying, to every corner of the crowd there are many people who trade for survival. Even though it is in such a busy position, the activities of Situ Rawa binong are still awake to its natural beauty, and has a series of cultural activities, sports facilities, and until it becomes a gathering place for communities or families, who want to relax from the density of activities that have been carried out. However, even though it is close to dense activity facilities, Rawa Binong Lake looks deserted from year to year from visitors who travel, after doing research and observation, it looks like a quiet atmosphere due to the lack of adequate infrastructure. From the time of the cultural activities that are often carried out every year, fewer and fewer people are willing to attend and attend the event. In response to this, the concept of a design design that can make the Rawa Binong Lake become crowded with visitors. As well as maintaining the preservation of nature and cultural activities. The author conducts research and makes considerations with various other tourist attractions. and the concept of an idea emerged, a design study to make Situ rawa binong managed as a tourist spot properly and not lost the existence of culture and natural beauty the author will promote the concept of Ecological Architecture.Which will create a beautiful tourist spot and maintain the beauty of the natural surroundings around the Rawa Binong. Keywords: Planning, Design, Ecological Architecture, Situ Rawa Binong